2002
DOI: 10.1590/s1519-38292002000300006
|View full text |Cite
|
Sign up to set email alerts
|

Aleitamento materno e condições socioeconômico-culturais: fatores que levam ao desmame precoce

Abstract: OBJETIVOS: avaliar o aleitamento materno, ressaltando os fatores que levaram ao desmame precoce conforme as condições socioeconômico-culturais. MÉTODOS: analisou-se uma amostra de 599 crianças e seus responsáveis que procuraram o Pronto Socorro do Instituto da Criança, São Paulo, de agosto a dezembro de 1998. Utilizou-se um questionário incluindo: idade, profissão e escolaridade dos pais, condições de moradia, renda familiar, trabalho materno, duração da amamentação exclusiva, introdução de novos alimentos, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
63

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 18 publications
(27 reference statements)
0
22
1
63
Order By: Relevance
“…São vários os fatores que estão interligados com o abandono desta prática alimentar, agindo de forma negativa ou positiva, sendo os principais: nível socioeconômico, grau de escolaridade da mãe, idade da mãe, trabalho materno, urbanização, condições do parto, incentivo do cônjuge e parentes, bem como a intenção da mãe de amamentar e experiência anterior a esta (ESCOBAR et al, 2002;ARAÚJO et al, 2008).…”
unclassified
“…São vários os fatores que estão interligados com o abandono desta prática alimentar, agindo de forma negativa ou positiva, sendo os principais: nível socioeconômico, grau de escolaridade da mãe, idade da mãe, trabalho materno, urbanização, condições do parto, incentivo do cônjuge e parentes, bem como a intenção da mãe de amamentar e experiência anterior a esta (ESCOBAR et al, 2002;ARAÚJO et al, 2008).…”
unclassified
“…However, as important as breastfeeding is exclusive breastfeeding, at least up to the child's six month of age, as recommended by WHO. This fact is corroborated by a study (15) that identified a higher percentage of children who breastfed for more than four months among working mothers with a high level of education.…”
Section: Discussionmentioning
confidence: 61%
“…However, removal of part of the breast tissue and internal tissue scarring, with fibrosis, may impede milk from being removed from ducts. In clinical practice, many women with breast reduction do not succeed in breastfeeding (15) . Yet, breastfeeding should be encouraged because some women who undergo surgery are able to breastfeed.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is clear that the oral breathing syndrome is a problem that affects all social layers of the population, where socioeconomic factors play a very important role, starting on prevention, with breastfeeding 44,45 which contributes to the child's immunization and the adoption of a proper respiratory pattern, all the way to creating opportunities for early diagnosis by providing access to information and health care.…”
Section: Discussionmentioning
confidence: 99%